MANAGEMENT OF FLOODS MONSOON 2010 AFFECTED POPULATION AT COMBINED MILITARY HOSPITAL, RISALPUR: Floods Monsoon 2010 - Younas, Muhammad; Rafique, Sibtain; Sohail, Amir; Almas, Danish (Pakistan Armed Forces Medical Journal, 2014)
Objective: The objective of this study was to evaluate the type of patients and procedures carried out on flood affected population near Risalpur and Nowshera in monsoon 2010. Study Design: Descriptive study. Place and Duration of the Study: Medical relief camps established at Government Technical Training College (TTC) near Kabul River Nowshera Kalan, and Federal Government Boys High School (FGS) at Risalpur Garrison and Combined Military Hospital (CMH) Risalpur from 29th July 2010 to 10th October 2010. Patients and Methods: Management of cases was divided into 2 phases. Phase 1 comprised of initial 6 days at TTC and phase 2 comprised of work at FGS from 7th day onwards till culmination of relief activity. Data was summarized on the basis of total number of patients rescued, sustained injuries, carried out procedures, detained, admitted and referred / transferred cases. Frequencies and percentages were used to describe the data. Results: Total number of patients managed during this flood relief operation were 8308. During first phase a total of 3863 cases including 969 males, 1419 females and 1495 children were treated at TTC Nowshera, while during second phase a total of 4425 flood affected cases including 1227 males,1929 females and 1269 children were managed at FGS Risalpur Garrison and CMH Risalpur. During this operation at CMH, 1024 patients were treated as outdoor cases, 74 patients were detained, 51 were admitted, 40 cases where referred while 4 cases were evacuated to DHQ Hospital/ CMH Mardan, 950 laboratory tests and 104 X-Rays/ USG were carried out. Gynecological services were of great importance as 3 caesarian sections, 18 normal vaginal devilries and 6 dilatations and curettages were performed. Conclusion: Medical services for disaster management were helpful to flood affected population in need of hour. Prompt medical treatment and early evacuation remains the mainstay. Emergency reproductive health care services should also be incorporated in effective disaster management plans.